Taxation and supplier networks: Evidence from India - Lucie Gadenne; Tushar K. Nandi; Roland Rathelot (Institute for Fiscal Studies (IFS), 2019)
Do tax systems distort firm-to-firm trade? This paper considers the effect of tax policy on supplier networks in a large developing economy, the state of West Bengal in India. Using administrative panel data on firms, including transaction data for 4.8 million supplier-client pairs, we first document substantial segmentation of supply chains between firms paying Value-Added Taxes (VAT) and non-VAT-paying firms. We then develop a model of firms' sourcing and tax decisions within supply chains to understand the mechanisms through which tax policy interacts with supply networks. The model predicts partial segmentation in equilibrium because of both supply-chain distortions (taxes affect how much firms trade with each other) and strategic complementarities in firms' decision to pay VAT. Finally, we test the model's predictions using variations over time within-firm and within supplier-client pairs. We find that the tax system distorts firms' sourcing decisions, and evidence of strategic complementarities in firms' tax choices within supplier networks. These two mechanisms explain a substantial share of the supply chain segmentation that we observe
Keywords: 330